Avoiding a feared stimulus: Modelling costly avoidance of learnt fear in a sensory preconditioning paradigm - Wong, Alex H.K.; Pittig, Andre (Biological Psychology, 2022)
Avoidance of learnt fear prevents the onset of a feared stimulus and the threat that follows. In anxiety-related disorders, it turns pathological given its cost and persistence in the absence of realistic threat. The current study examined the acquisition of costly avoidance of learnt fear in healthy individuals (n = 45), via a sensory preconditioning paradigm. Two neutral preconditioning stimuli (PSs) were paired with two neutral conditioned stimuli (CSs). One CS then came to predict an aversive outcome whereas the other CS came to predict safety. In test, participants engaged in stronger avoidance to the PS associated with the fear-related CS than the PS associated with the safety-related CS. Of note, executing behavioral avoidance led to missing out a competing reward, thus rendering avoidance costly. The results also provide preliminary evidence that threat anticipation and a negative change in valence play a role in driving costly avoidance of learnt fear. Future studies should examine how avoidance of learnt fear maintains pathological anxiety.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Anxiety; Avoidance; Costly avoidance; Fear conditioning; Higher-order conditioning; Threat anticipation